Earthquake Vulnerability Assessment in Sanma Island, Republic of Vanuatu - Jafar, Jafar (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this assessment is to identify which councils on Sanma Island are vulnerable to earthquake hazards. To measure vulnerability, it is necessary to identify certain contributing components, including exposure, sensitivity, and adaptive capacity. Exposure and sensitivity contribute to increasing the vulnerability, while adaptive capacity contributes to decreasing the vulnerability. Using this scheme, we identify specific variables for each component. These variables are called vulnerability variables. Next, we employ the Analytic Hierarchy Process (AHP) to obtain scores for each variable. Following the vulnerability assessment, five councils are categorized as areas with high vulnerability scores, including Canal-Fanafo, East Malo, East Santo, West Malo, and West Santo. This is because these areas are relatively close to the source of the threat (earthquake hazard). Moreover, these councils have a limited number of public facilities.